HUBUNGAN KELENGKAPAN INFORMASI MEDIS DENGAN KEAKURATAN KODE DIAGNOSIS PENYAKIT DIABETES MELLITUS DI RUMAH SAKIT X BLITAR - Dewi, Cindy Shinta; Akbar, Prima Soultoni; Alvionita, Chyntia Vicky (Politeknik Kesehatan Kemenkes Malang, 2024)
The completeness of medical information and the accuracy of medical records are crucial. If the medical information in a record is incomplete, the resulting diagnosis codes will be inaccurate. Inaccurate diagnosis codes lead to incorrect data and generate wrong charges, thus affecting the quality of statistical data and health cost payments. This study aims to examine the relationship between the completeness of medical information and the accuracy of Diabetes Mellitus diagnosis codes at X Hospital Blitar. This research employed a quantitative observational design with a cross-sectional approach, with a sample of 68 medical records of inpatient Diabetes Mellitus cases from January to October 2023. The percentage of complete medical information was 77.9%, while the incomplete information was 22.1%. The accuracy of Diabetes Mellitus diagnosis codes was 76.5%, and the inaccuracy rate was 23.5%. The results of this study indicate a statistically significant relationship between the completeness of medical information and the accuracy of Diabetes Mellitus diagnosis codes at X Hospital Blitar (p<0.001, OR = 49.000), affecting the accuracy of the Diabetes Mellitus diagnosis codes. The conclusion of this study is that there is a relationship between the completeness of medical information and the accuracy of Diabetes Mellitus diagnosis codes at X Hospital Blitar.